2014
DOI: 10.1186/1880-5981-66-22
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the geoid model over Japan using integral formulae and combination of GGMs

Abstract: An improved high-resolution gravimetric geoid model covering the four main islands of Japan (Hokkaido, Honshu, Shikoku, and Kyushu) was developed on a 1 × 1.5 arc-minute grid from EGM2008, GOCO02S/EGM2008, and terrestrial gravity data. A modified form of the Stokes-Helmert scheme was applied for the determination of the geoid using an empirically determined optimal spherical cap size. Handling of the topographical effects on gravity was accomplished using the integral formulae of Martinec and Vaníček, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…differences between gravimetric and GPS/levelling geoid undulations using Helmert orthometric heights (Odera and Fukuda 2014) are also given in Table 2. Table 2 shows that there is a slight improvement in the standard deviation in all the regions (Hokkaido, North Honshu, Central Honshu, West Honshu, Shikoku and Kyushu), with Central Honshu (a mountainous region) having the largest improvement (from ±7.1 to ±6.9 cm), when rigorous orthometric heights are used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…differences between gravimetric and GPS/levelling geoid undulations using Helmert orthometric heights (Odera and Fukuda 2014) are also given in Table 2. Table 2 shows that there is a slight improvement in the standard deviation in all the regions (Hokkaido, North Honshu, Central Honshu, West Honshu, Shikoku and Kyushu), with Central Honshu (a mountainous region) having the largest improvement (from ±7.1 to ±6.9 cm), when rigorous orthometric heights are used.…”
Section: Resultsmentioning
confidence: 99%
“…The rigorous orthometric heights at the 816 GPS/levelling points are then used in the comparisons between gravimetric and GPS/levelling geoid undulations (Table 2) using the recent geoid model over Japan (Odera and Fukuda 2014). For comparison purposes, the statistics of the Figure 5 Spatial distribution of corrections to Helmert orthometric heights using 816 precise levelling points over Japan (units in cm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development and applications of LSC techniques in geodesy and related fields have been studied by several authors (e.g. Krarup 1969;Moritz 1973;Tscherning 1976;Kearsley 1977;Moritz 1980;Knudsen 1987;Forsberg 1987;Schaffrin 1989).…”
Section: Planar Fitting and Offsets Methodsmentioning
confidence: 99%
“…Following the successful operation of a dedicated satellite gravity mission, called-Gravity field and steady-state Ocean Circulation Explore (GOCE)-during 2009-2013, a number of GGMs with high accuracy and high spatial resolution have been released by research institutes and universities. Odera and Fukuda (2014) first employed a GOCE-based GGM for the determination of the geoid undulation over the Japanese archipelago and demonstrated that utilization of the latest GOCE-based GGM could improve the accuracy of the gravimetric geoid model for Japan.…”
Section: Introductionmentioning
confidence: 99%